UPAYA GREENPEACE DALAM MENCEGAH KEBAKARAN HUTAN DI PULAU KALIMANTAN - Amirudin, Muhamad; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The purpose of this research was to analyze Greenpeace's approaches and efforts in preventing forest fires that occur in Kalimantan. Greenpeace serves as one of the environmental non-governmental organizations in Indonesia. This study is a qualitative research that uses the theory of NGO roles to examine the efforts made by Greenpeace in preventing forest fires in Kalimantan. In this research, the analysis level used is group analysis. Data collection was carried out using document analysis methods sourced from several books, journal articles, and other references relevant to the efforts made by Greenpeace in preventing forest fires on the island of Kalimantan. The research show that Greenpeace, as one of the NGOs focusing on environmental issues in Indonesia, has taken several measures to prevent forest fires in Indonesia. Greenpeace fulfills its role as an NGO through various means, such as providing assistance services and technical expertise, directly participating in operational activities, conducting analyses related to environmental issues, campaigning to raise public awareness and encourage action on various environmental issues, and facilitating negotiations between civil society and the government. Keywords: Greenpeace, Forest Fires, Kalimantan Island, International NGO